Perceptual and behavioural dimensions: measuring brand equity consumer based. Issue 4 (3rd October 2016) - Rodrigues, Paula; Martins, Francisco Vitorino
Abstract : Purpose: The purpose of this paper is to propose a brand equity measurement model in the consumers' mind. The measurement model separates the perceptual component of the behaviour component of individuals in their preferences for brands. That is, as a result of a set of perceptions, consumers create a brand equity that will be realised in loyal behaviour and in their willingness to pay a premium price for a brand. Design/methodology/approach: A measurement model of brand equity using the methodology of SEM is proposed. Two samples were used, one for the estimation and another one for the validation of the proposed model, with 272 observations each. The sample is constituted by consumers of five denim clothing brands that have their own chain of stores in Portugal. Findings: Results show that the model is statistically valid and that perceptual aspects should be separated from behavioural aspects in brand equity measurement based on consumers' mind. Originality/value: The originality of the model is the division of constructs into perceptual constructs (inputs), and of behaviour constructs (outputs) of brand equity. By doing this, the model tries to answer two important aspects of entrepreneurial management: which are the explanatory variables of brand equity and how could that be translated into an answer, for the consumer.